2014
DOI: 10.1126/scitranslmed.3009759
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota influences blood-brain barrier permeability in mice

Abstract: Pivotal to brain development and function is an intact blood-brain barrier (BBB), which acts as a gatekeeper to control the passage and exchange of molecules and nutrients between the circulatory system and the brain parenchyma. The BBB also ensures homeostasis of the central nervous system (CNS). We report that germ-free mice, beginning with intrauterine life, displayed increased BBB permeability compared to pathogen-free mice with a normal gut flora. The increased BBB permeability was maintained in germ-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

22
1,331
6
12

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 1,780 publications
(1,466 citation statements)
references
References 58 publications
22
1,331
6
12
Order By: Relevance
“…72 These defects in permeability persisted into adulthood, as demonstrated by leakage of Evans blue dye into the brain parenchyma 71 and seminiferous tubules of the testis of mature mice. 72 This leakiness was associated with reduced expression of TJ proteins 71,72 : in the BBB, expression of claudin-5 and occludin was lower, while that of ZO-1 was unchanged; and in the BTB, expression of occludin and ZO-2 was lower. 72 Moreover, electron microscopy revealed that TJ in the brain of GF adult mice were disorganized.…”
Section: Influence Of Microbiota On the Intestinal Barriermentioning
confidence: 99%
See 4 more Smart Citations
“…72 These defects in permeability persisted into adulthood, as demonstrated by leakage of Evans blue dye into the brain parenchyma 71 and seminiferous tubules of the testis of mature mice. 72 This leakiness was associated with reduced expression of TJ proteins 71,72 : in the BBB, expression of claudin-5 and occludin was lower, while that of ZO-1 was unchanged; and in the BTB, expression of occludin and ZO-2 was lower. 72 Moreover, electron microscopy revealed that TJ in the brain of GF adult mice were disorganized.…”
Section: Influence Of Microbiota On the Intestinal Barriermentioning
confidence: 99%
“…Remarkably, these barriers could be "sealed" by recolonizing their intestines with fecal material from the control mice. Colonization with bacterial strains that produce only butyrate (Clostridium Tyrobutyricum) or acetate/probionate (Bacteroides thetaiotaomicron) restored the integrity of the brain parenchyma 71 and seminiferous tubules of the testis 72 as shown by exclusion of Evans blue dye. Furthermore, the protein components of the TJ complexes in these barriers were restored to control levels by either such colonization or butyrate alone.…”
Section: Influence Of Microbiota On the Intestinal Barriermentioning
confidence: 99%
See 3 more Smart Citations